International investment law: protection of foreign investors - Eishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (LexisNexis Malaysia Sdn Bhd, 2025)
This chapter aims to define international investment law, examine its sources, and explore its main principles and their legal foundations. The chapter also delves into the rights afforded to foreign investors, the structure and effectiveness of dispute settlement mechanisms, and the broader implications for both host states and investors.